2009
DOI: 10.1002/psc.1125
|View full text |Cite
|
Sign up to set email alerts
|

Membrane permeability and antimicrobial kinetics of cecropin P1 against Escherichia coli

Abstract: The interaction of cecropin P1 (CP1) with Escherichiacoli was investigated to gain insight into the time-dependent antimicrobial action. Biophysical characterizations of CP1 with whole bacterial cells were performed using both fluorescent and colorimetric assays to investigate the role of membrane permeability and lipopolysaccharide (LPS) binding in lytic behavior. The kinetics of CP1 growth inhibition assays indicated a minimal inhibitory concentration (MIC) of 3 microM. Bactericidal kinetics at the MIC indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 30 publications
5
27
0
Order By: Relevance
“…The region encompassing these charged residues adopts a helical confirmation. The NA-CATH structure appears to be similar to previous straight α-helical AMPs and there is strong evidence supporting a membrane disruption behavior via membrane thinning, defects, transient pores, and carpet model dissolution [20,23,32,88]. Our fluorescence and microscopy data indicate that NA-CATH functions in a similar manner.…”
Section: Resultssupporting
confidence: 70%
“…The region encompassing these charged residues adopts a helical confirmation. The NA-CATH structure appears to be similar to previous straight α-helical AMPs and there is strong evidence supporting a membrane disruption behavior via membrane thinning, defects, transient pores, and carpet model dissolution [20,23,32,88]. Our fluorescence and microscopy data indicate that NA-CATH functions in a similar manner.…”
Section: Resultssupporting
confidence: 70%
“…The results revealed that Mdc can mediate rapid killing of MDR- A. baumannii in 30 min and resulted in log orders of cell complete lysis at a concentration as low as 4  μ g/mL (Figure 2). These observations were in agreement with previous results obtained in other multidrug-resistant strains of bacteria with antimicrobial peptides [17]. …”
Section: Discussionsupporting
confidence: 93%
“…Many of these belong to the family of cecropin peptide [16]. Previous studies in cecropin and its related peptides demonstrate that formation of membrane-spanning pores that disrupt the cell membrane of the bacteria seems to be the most likely mechanism [17, 18]. However, the details surrounding the mechanism of bactericidal still need to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows that dead bacteria and those treated with peptide (4x MIC) incorporated PI (63.5%), whilst bacteria without treatment did not incorporate PI. The AMP cecropin, which has been reported to induce inner membrane perturbation (Chen et al, 2003; Arcidiacono et al, 2009), induced high PI incorporation (83.75%) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 96%
“…Maximum permeability was determined by evaluating cells pre-treated with cecropin (3 μM). Permeability rate was evaluated by ONPG hydrolysis, measuring absorbance at 405 nm in 30 min intervals for up to 3 h (Arcidiacono et al, 2009). …”
Section: Methodsmentioning
confidence: 99%